PEMETAAN GEOLOGI, ALTERASI, MINERALISASI DAN KERAPATAN URAT KUARSA PADA BENCH 210 UNTUK MENGETAHUI PENGARUH KERAPATAN URAT KUARSA TERHADAP MINERALISASI DAN NILAI KADAR TEMBAGA ENDAPAN PORFIRI CU-AU BATU HIJAU, SUMBAWA, NTB - Laraswati Jiwatami Dwi Kusuma (Program Studi Teknik Geologi, Fakultas Teknik, Universitas Diponegoro, 2013)
Porphyry deposit is one of hydrothermal deposit which has potential to yield economic minerals such as gold, copper and molybdenum. Studying thegeological concept of porphyry deposit like lithology aspect, type andcharacteristic of alteration, mineralization style and vein type can laid to conceptof mineralization environmental that can generate ore. Study of mineralization inporphyry deposit also need quartz vein density analysis to determine the highgrade and low grade mineralization zone.This research is purposed to determine the distribution of lithology, zone of alteration and the relationship between quartz vein density and mineralizationin Batu Hijau Porphyry Deposit. Furthermore the result of the research can bethe consideration for geologist to mine the high grade materials.The methods that used to analyze the relationship between quartz vein density and mineralization on Bench 210 Batu Hijau Porphyry Deposit are bydoing highwall mapping on north and east side of Bench 210 open pit and logging121 geological cores which passed bench 210 (each core’s length 15 meters).From the approach above, known that lithology from old to young are Volcanic wallrock, Diorite Intrusion, Intermediate Tonalite Intrusion and YoungTonalite Intrusion. Megascopic and microscopic observation show that alterationon research area can be divided into 5 alteration zones, they are: Partial BiotitZone (potasic zone), Secondary Biotite Zone(potasic zone), Pale Green Mica Zone(argilic zone), Chlorite-Epidote Zone (philic zone) and Feldspar Destructive Zone(propilic zone). Mineralization that occurs in research area is copper-sulfidemineralization. Bornite (Cu5FeS4) and Chalcopyrite (CuFeS2) are the maincopper sulfide ore and Pyrite as gangue mineral. Quartz vein density zone onresearch area is divided to very abudant quartz vein density (10-15%), abundantquartz vein density (5-9,9%), moderate quartz vein density (3-4,9%) and rarequartz vein density (0,3-2,9%). There are positive relationship between quartzvein distribution and Cu assay content. The higher quartz vein density in Bench210 is the higher Cu assay content and generally occurs in Bornite dominatedzone. And the lower quartz vein density is the lower Cu assay content andgenerally occurs in Pyrite dominated zone.